Career Development and Competence Towards Increasing Job Satisfaction With the Mediation of Organizational Commitment in Banyumanik District - Putranto Anugrah; Heru Sulistyo (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
Because it affects teaching quality, teacher performance, and eventually the overall quality of education, teacher job satisfaction in schools is very important.  Teachers that are happy tend to be more driven, effective, and capable of fostering a supportive learning environment for their pupils.  The purpose of this research is to partly and concurrently examine the effects of competence, career growth, and normative commitment on elementary school teachers' work satisfaction in the Ayodya cluster in the Banyumanik district of Semarang City.  Using a saturation sampling strategy, the study's sample consisted of all 88 instructors in the Ayodya cluster.  A survey-based quantitative research methodology was used.  A questionnaire with a Likert scale of 1–5 was used to gather the data.  Using SPSS 23, data analysis methods included multiple regression, t-tests, F-tests, and classical assumptions.  According to the study's findings, work satisfaction is highly influenced by competence, career advancement, and normative commitment, in that order.  At the same time, primary school teachers' work satisfaction in Banyumanik, Semarang City's Ayodya cluster is greatly influenced by career growth, competence, and normative commitment.